PENGARUH PRODUK, HARGA, DAN LOKASI TERHADAP KEPUTUSAN PEMBELIAN MIE RATE “RAJA TEGA” BALONGPANGGANG GRESIK - Fahmi Fahrizal Pradianto; Hendrik Rizqiawan (Jurnal Ekonomi, Bisnis dan Social, 2023)
This research aims to analyze the effect of product, price and location on purchase decision. The sample of this research is the people who consume the product of Mie Rate "Raja Tega" Balongpanggang Gresik. The sampling technique in this research used the theory of Sugiono with a non-probability sampling technique, namely purposive sampling totaling 100 respondents. Statements were given using a questionnaire. Responses from respondents were analyzed using Statistical Product and Service Solutions (SPSS) version 21. This study research multiple linear regression analysis. Hypothesis testing was carried out partially (t-test) and simultaneously (F-test). The results of this study indicate that product, price, and location simultaneously have a positive and significant effect on purchasing decisions for the Mie Rate "Raja Tega" Balongpanggang Gresik product. Partially Product affects the Purchase Decision. While the Price and Location have positive effect but not significant on purchase decisions. The independent variables in this research have an influence of 58,7% on purchase decisions and the rest are influenced by other variables that aren’t in this research